Left atrial appendage and atrial septal occlusion in elderly patients with atrial septal defect and atrial fibrillation. Issue 11 (7th September 2020) - Leong, Ming Chern; Kandavello, Geetha; Husin, Azlan; Perumal, Deventhiren; Kaur Khelae, Surinder
Abstract: Background: Elderly patients with atrial septal defect (ASD) often present with chronic atrial fibrillation and large left to right shunt. This study reports the experience of left atrial appendage (LAA) and ASD closure in patients with significant ASD and chronic atrial fibrillation. Methods: We report six consecutive elderly patients with chronic atrial fibrillation and significant ASD who underwent LAA and fenestrated ASD closure from January 1, 2014 until December 31, 2019. All periprocedural and long‐term (>1 year) outcomes were reported. Results: Six patients (male: 33.3%; mean age: 66.8 ± 3.3 years) were included. Mean CHADS2, CHA2 DS2 ‐VASc, and HAS‐BLED scores were 2.33 ± 0.82, 3.83 ± 0.75, and 1.83 ± 0.75. Four patients underwent simultaneous procedure, while two patients underwent a staged procedure. Procedural success was achieved in all patients. Total occlusion was achieved during LAA occlusion without device embolization prior to ASD closure. Patients who underwent simultaneous procedure had a shorter total hospital stay and lower total hospital stay. During a follow‐up period of 32.8 ± 19.4 months, both the devices were well seated. No device‐related thrombosis or erosion reported. All patients remained in atrial fibrillation. No patients experienced any thromboembolic stroke or transient ischemic attack. Conclusions: LAA and ASD closure is feasible and can be safely performed in the same seating in elderly patients with a significant ASD.